The effect of temperature on the stability of PCSK-9 monoclonal antibody: an experimental study - Kongmalai, Tanawan (Lipids Health Dis, 2021)
BACKGROUND: PCSK9 monoclonal antibody lowers plasma PCSK9 and LDL-cholesterol levels. The manufacturers recommend drug storage at 2–8 °C, and not above 25 °C. This study aimed to investigate drug stability at various temperatures that this drug could be exposed to during medication handling and transportation in tropical countries. METHODS: Alirocumab and evolocumab were tested in 3 study conditions: room temperature (RT), cooler device with cold pack, and freeze-thaw for 9 and 18 h. Heated drugs were used as negative control. Free plasma PCSK9 levels from 9 hyperlipidemia subjects were measured with ELISA. RESULTS: Average subject age was 49.2 ± 18.4 years. Percent PCSK9 inhibition significantly declined in heated drugs compared to baseline. Average RT during the study period was 30.4 ±2.6 °C. Change in percent PCSK9 inhibition of PCSK9 mAb at RT from baseline was − 5.8 ± 4.4% (P = 0.005) and − 11.0 ± 8.9% (P = 0.006) for alirocumab at 9 h and 18 h, and − 9.7 ± 11.8% (P = 0.04) and − 15.1 ± 14.3% (P = 0.01) for evolocumab at 9 and 18 h, respectively. In contrast, there were no significant changes in percent PCSK9 inhibition from baseline when PCSK9 mAb was stored in a cooler. In freeze-thaw condition, changes in percent PCSK9 inhibition from baseline to 9 and 18 h were − 5.2 ± 2.9% (P = 0.001) and − 2.6 ± 4.9% (P = 0.16) for alirocumab, and − 1.8 ± 4.2% (P = 0.24) and 0.4 ± 6.1% (P = 0.83) for evolocumab. CONCLUSION: Proper drug storage according to manufacturer’s recommendation is essential. Drug storage at RT in tropical climate for longer than 9 h significantly decreased drug efficacy; however, storage in a cooler device with cold pack for up to 18 h is safe. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12944-021-01447-3.